Linking Stock Prices and Macroeconomic Variables in Malaysia - Ng, Yong Chew; Mori Kogid; Dullah Mulok (Universiti Malaysia Sabah, 2018)
This study investigates the relationship between stock prices and selected macroeconomic variables from January 1980 to May 2017 using monthly data comprising 449 observations. The study employs several econometric tests such as unit root test for stationarity test, cointegration test and Granger causality test to determine the long- and short-run relationships between stock prices and macroeconomic variables. The result of the Johansen cointegration test shows that all the macroeconomic variables are cointegrated with stock prices in the long-run. Moreover, the Granger causality tests show that only exchange and inflation rates significantly Granger cause stock prices in the short run. However, the money supply and interest rate had no causal relationship with stock prices.